Conflicting interests among Indonesian journalists and churnalism in the platformed media ecosystem - Siregar, Ballian; Latif, Das'ad; Ramli, Muhammad Ruslan; Nugroho, Julian; Solihin, Olih (Universitas Bunda Mulia, 2026)
Social media has changed how reporters do their jobs. At first, people used social media to talk to each other and make friends. Social media has replaced radio, newspapers, television, and online news sites as the main way people get their news. This change worries professional journalists because it could make information less accurate, take away editorial control, and change the values of journalism. This study aims to investigate Indonesian journalists' views on the prevalence of social media within the media ecosystem and its effects on journalistic quality. This research utilizes a constructivist framework, incorporating qualitative methodologies and case studies. The study's findings indicate that (1) the evolution of media identity, once a bastion of truth, has transitioned to social media regulated by algorithms; (2) audiences exhibit enhanced autonomy while still being susceptible to deficiencies in information literacy; and (3) digital algorithms now profoundly affect the audience's media experience, necessitating a reevaluation and redefinition of media professionalism in Indonesia.